The impact of negative interest rates on Nordic banks’ riskiness - Keski-Marttunen, Katriina Iida Sofie (My University, 2023)
This thesis examines if the negative interest rates increased Nordic banks’ risk-taking and whether there are specific factors that have affected to the overall riskiness of Nordic banks. The prolonged period of negative interest rate policy (NIRP) have raised concerns about the health of European banking sector and how negative deposit rates affect banks’ net worth and profitability. It is found that funding structure could affect banks’ risk appetite and especially banks with higher share of deposits and traditional business models, tend to increase their credit risk by lending to riskier borrowers. Previous literature find that the transmission of negative interest rates is not unambiguous and depends on the various bank specific characteristics and country specific factors. In order to measure banks’ risk taking behavior, the development of banks’ risky assets to total assets need to be examined. By using non-traditional difference-in-differences setup, Nordic banks’ risk- taking behavior can be assessed and compared to the non-NIRP-adopter countries. This paper focuses mainly on comparing differences in monetary policy across in broadly comparable countries. As found in the previous literature, it is expected that banks affected by NIRP reduce their loan prices, increase debt financing and by increasing their lending activity, banks are aiming to maintain their profitability. The empirical findings reported in this thesis suggest that after the implementation of negative interest rates, Nordic banks have had relatively healthy balance sheets and there has not been a clear shift to riskier lending to help the weak profitability. Furthermore, NIRP has had relatively similar effect on both treatment (Nordic banks) and control (non-NIRP-adopter banks) groups. To conclude, this thesis does not support the previous findings where negative interest rates have increased banks’ risk-taking significantly. However, the actual consequences of the ECB’s negative interest rate policy are still unknown. It will be difficult to predict will the banks’ stability be disturbed, when the record-high inflation rate is pushing the ECB to increase the policy rates at a rapid pace. When the interest rates take a steep upward turn, the maturity risk realizes and banks’ ability to pay interest to customers deposits endangers. Therefore, the spillover effects of the ECB’s expansionary monetary policy and the racing inflation might have long-lasting impact on the stability of the global banking sector.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance